Measuring the Meaning of Islamic Education Curriculum Development - Choiri, Moh. Miftachul; Sidiq, Umar (Al-Hayat: Journal of Islamic Education, 2023)
Curriculum, as a soft component, is vital as a guiding tool to achieve the vision and mission determined by each educational institution. Therefore, curriculum development for an educational institution should consider aspects of student development, community needs and developments in science and technology. This research wants to see how the head of the Madrasah Ibtidaiyah and the teachers in the Ponorogo Ma'arif Education Institute interpret the development of the Islamic Education curriculum so that various subjects in the Islamic Education family can be achieved according to the goals formulated. This study uses an interpretive paradigm through a qualitative approach, a case study type. Data collection techniques use in-depth interviews, observation and documentation. The analysis tool used is the qualitative analysis model of Miles and Huberman data reduction, data display and verification. I checked data validity using triangulation; credibility, transferability, dependability and confirmability. The study results show that the development of the Islamic Education curriculum is interpreted as a strategic activity to develop Madrasahs and link one component of the Islamic Education curriculum with other members. The development of the Islamic Education curriculum at Madrasah Ibtidaiyah within the Ponorogo Ma'arif Educational Institution follows the stages of curriculum development consisting of planning, organizing, implementing, human resources, control, and a comprehensive mechanism.